Inpatient prenatal yoga sessions for women with high-risk pregnancies: A feasibility study. (January 2020) - Dangel, Alissa R.; Demtchouk, Veronica O.; Prigo, Corinne M.; Kelly, Jeannie C.
Highlights: Prenatal yoga studies to date have been limited to the outpatient setting. This study explored the feasbility of expanding the option of prenatal yoga to a high-risk inpatient population. Abstract: Background: Antenatal hospitalization for pregnancy complications can result in significant stress for pregnant women and their families. Prenatal yoga has been investigated in the outpatient setting as a method to alleviate stress. This study was designed to investigate the feasibility of incorporating prenatal yoga into the inpatient environment for women hospitalized with pregnancy complications. Study design: High-risk women were recruited from the inpatient antepartum service at Tufts Medical Center (Boston, MA; March 2016 to February 2017) to evaluate the feasibility of an inpatient prenatal yoga program. The thirty-minute session was led by a certified instructor in a room adjacent to Labor and Delivery. Participants and antepartum nurses completed study questionnaires addressing logistics such as class duration and frequency. Perceived benefits of yoga were also explored. Results: Thirty-nine women were found eligible for this study and were consented for participation. Of these, fifteen (38%) participated in at least one yoga session. Responses to the to the post-class questionnaire by study participants indicated that the thirty minutes allocated for the yoga class was appropriate. Of the eight participants who responded to the discharge questionnaire, all indicated that the class was helpful with regards to stress reduction. Completed questionnaires by the antepartum nursing staff (n = 14) unanimously indicated that the yoga session was helpful for the patients and was not disruptive to medical care. Conclusion(s): Prenatal yoga is a technique that has been currently limited to the outpatient setting. This study provides a foundation for continued investigation of inpatient prenatal yoga for women hospitalized with pregnancy complications.